If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(3) * 5x = log(3) * 160 Reorder the terms for easier multiplication: 3 * 5glo * x = log(3) * 160 Multiply 3 * 5 15glo * x = log(3) * 160 Multiply glo * x 15glox = log(3) * 160 Reorder the terms for easier multiplication: 15glox = 3 * 160glo Multiply 3 * 160 15glox = 480glo Solving 15glox = 480glo Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-480glo' to each side of the equation. -480glo + 15glox = 480glo + -480glo Combine like terms: 480glo + -480glo = 0 -480glo + 15glox = 0 Factor out the Greatest Common Factor (GCF), '15glo'. 15glo(-32 + x) = 0 Ignore the factor 15.Subproblem 1
Set the factor 'glo' equal to zero and attempt to solve: Simplifying glo = 0 Solving glo = 0 Move all terms containing g to the left, all other terms to the right. Simplifying glo = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-32 + x)' equal to zero and attempt to solve: Simplifying -32 + x = 0 Solving -32 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + x = 0 + 32 x = 0 + 32 Combine like terms: 0 + 32 = 32 x = 32 Add '-1x' to each side of the equation. x + -1x = 32 + -1x Combine like terms: x + -1x = 0 0 = 32 + -1x Simplifying 0 = 32 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 29=-3+4x | | 13=-6w | | 8(x)/7+9+30 | | 9*u+7=5(u+3) | | 6(w+1)=2*w+34 | | 6x(6+4x)=26+x | | -8*v-2=-6(v-1) | | .125D-3(D-7)=5.125D-3 | | 21=-7*u+4(u+6) | | x^2-xy+3x^2+4xy= | | 2(v-7)+5*v=28 | | (x+1)(x-2)/x+3 | | 2(x+4)+3*x=-12 | | 7*y+23=4*y+8*y-22 | | x/5-12=4 | | -8=5x+3 | | k(2)-25=0 | | 2y+3=(y+21) | | 6*y+5=8*y+11 | | 28+19*x=-8+15*x | | 6x+8=11-4c | | -83=2*v-15*v-18 | | x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x |